Digitalization of management decisions in local government authorities - Nurmurodov Zafarjon Nurmurod ugli (International Journal on Human-Computing Studies, 2021)
The article addresses the issue of establishing a practice of preparing and making decisions through the electronic system "E-Qaror" by digitizing the activities of local government.